Improving substance use disorder care: Service providers' perceptions on barriers to drug use treatment in the Western Province Sri Lanka - Nawaratne, Sashiprabha; Vidanapathirana, Janaki (Asian Journal of Interdisciplinary Research, 2023)
The increasing prevalence of drug use as well as a large number of drug users not seeking treatment is a major concern in Sri Lanka. Drug abuse treatment providers are in a unique position to identify barriers that deter drug users from accessing their services. Hence this study aimed to explore the service providers' perceptions of the barriers to drug users accessing treatment services. A qualitative study was conducted with 12 purposely selected service providers from drug treatment centres representing government, non-government, health and non-health sector institutions in the Western Province. In-depth interviews using a semi-structured questionnaire were used as the data collection method. All interviews were conducted by the Principal Investigator and were manually and digitally recorded. Interview data were transcribed and analysed using the inductive thematic analysis method. Five main themes emerged from the data. The main themes were easily identified as being drug user-related factors and service provider-related factors. Poor drug-related health literacy and negative environmental influences were drug user-related factors which service providers perceived as barriers. Service providers perceived that poor provider training, bureaucratic challenges and poor interagency cooperation are barriers within their own programmes that act as barriers for drug users when accessing treatment services. Service providers perceived that drug users who require treatment confront numerous barriers when accessing the help, they need. It is important to address these barriers in order to improve treatment services for this marginalized group.